Cellophane strip for correction of portosystemic shunt in a canine: Case report - Laverde, Néstor (2022)
A case of an 8-month-old Shih Tzu canine was referred to ASMEVET veterinary hospital in the city of Tunja, Colombia with a presumptive diagnosis of portosystemic shunt. The owner reported that the patient wanders at night, is not resting, has been vomiting, had convulsions and leaned his head against the walls. Clinical examination revealed dehydration, tachycardia, tachypnea, sialorrhea, disorientation and abdominal pain. Doppler ultrasonography was performed where the communication between the portal vein and the caudal vena cava was found. An exploratory laparotomy was performed to visualize the anomalous communication between the portal vein and the caudal vena cava, and a cellophane strip was installed around the anomalous vessel. After 60 days of surgery, blood samples were taken to measure pre and postprandial ammonium and bile acids, yielding values within normal blood ranges.